Three Organic/Inorganic Nanolayers on Flexible Foam Allow Retaining Superior Flame Retardancy Performance Upon Mechanical Compression Cycles - Carosio, Federico; Fina, Alberto (Frontiers in Materials, 2019)
The water-based deposition of flame retardant coatings on flexible polyurethane foams has attracted great interest among scientific community due to the great performances associated with this technology. Unfortunately, this approach results inefficient as it requires a high number of steps in order to achieve the desired properties. In this paper, we report the production of flame retardant foams by means of the simple deposition of only three nanoparticles containing layers. The composition and order of the deposited layer has been designed in order to provide specific flame retardant actions, targeting delayed release of polymer decomposition products to the gas phase, dilution of these flammable products with water and intumescent barrier formation. The morphology of the coated foams after the adsorption of each layer has been investigated by scanning electron microscopy, demonstrating the ability of each adsorbed layer to completely wrap the complex 3D structure of the foam. This three layers based coating produces a protective exoskeleton that is capable of self-extinguishing the flame in standard flammability tests, leaving the foam almost unaffected (final residue 98%). In forced combustion tests by cone calorimetry, treated foams showed considerably reduced combustion rates, with reduced peak of heat release rate (-50%) as well as consistent reduction in the smoke optical density (-51%) and the total smoke release (-34%). In addition, treated foams have been demonstrated to maintain the ability to self-extinguish the flame as well as reduced combustion rates and smoke production even after being subjected to 100 compression cycles.